2019
DOI: 10.1186/s13223-019-0384-8
|View full text |Cite
|
Sign up to set email alerts
|

Methodological evaluation of human research on asthmagenicity and occupational cleaning: a case study of quaternary ammonium compounds (“quats”)

Abstract: In this paper, we review methodological approaches used in studies that evaluated the association between occupational exposure to quaternary ammonium compounds (quats) and occupational asthma. This association is of interest because quats are a common active ingredient of disinfectants and have been linked to work-related asthma in some circumstances. However, any evidence-based assessment of an exposure-outcome association needs to consider both strengths and limitations of the literature. We focus on public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…OA induced by triclosan was documented by positive SIC [46]. A recent review evaluated the association between occupational exposure to quaternary ammonium compounds and OA and concluded that currently it is difficult to define this link in raison of the limited data in the literature, studies realized in specific populations (e.g., farmers or cleaners), poor understood pathogenesis and the presence of many confounders (other chemical and biological agents) in the workplace as possible asthmagens [48].…”
Section: Oa-induced By Lmw Sensitizing Agentsmentioning
confidence: 99%
“…OA induced by triclosan was documented by positive SIC [46]. A recent review evaluated the association between occupational exposure to quaternary ammonium compounds and OA and concluded that currently it is difficult to define this link in raison of the limited data in the literature, studies realized in specific populations (e.g., farmers or cleaners), poor understood pathogenesis and the presence of many confounders (other chemical and biological agents) in the workplace as possible asthmagens [48].…”
Section: Oa-induced By Lmw Sensitizing Agentsmentioning
confidence: 99%
“… 30 , 31 Human epidemiological studies on the health effects of exposure to QACs are limited and mostly include occupational exposure studies linking QACs to exacerbation of asthma-related symptoms. 37 39 In a recent study, the concentrations of BACs and DDACs in human blood were associated with the increase in inflammatory cytokines, decrease in the mitochondrial function, and disruption of cholesterol homeostasis in a dose-dependent manner at levels detected in the general population. 40 …”
Section: Introductionmentioning
confidence: 99%
“…The most complete assessment of the occupational asthma question was undertaken by LaKind and Goodman. 63 Among issues they grappled with were as follows:…”
Section: Epidemiology Studies: Occupational Asthmamentioning
confidence: 99%
“…With these in mind to guide their assessment, LaKind and Goodman (2019) 63 reported their review of 18 investigations, including population studies and both case reports and challenge studies of individual patients and assessed the association between QACs and asthma occurrence in various subject groups. Interestingly, they noted that "studies of occupational groups with the highest potential for QAC exposure (e.g., cleaners and farmers) do not consistently report increased incidence of asthma attributable to QACs."…”
Section: Epidemiology Studies: Occupational Asthmamentioning
confidence: 99%